2007
DOI: 10.1021/ma070398k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electroluminescent Properties of Poly(p-phenylenevinylene)s with 3‘,3‘-Diheptyl-3,4-propylenedioxythiophene Pendant Group for Light-Emitting Diode Applications

Abstract: Using the Gilch polymerization method, we synthesized a new series of green electroluminescent polymer, poly[1,4-{2-(3,3‘-diheptyl-3,4-propylenedioxythiophen-2-yl)}phenylenevinylene], poly(PDOT−PV), which is a series of fully conjugated poly(p-phenylenevinylene) derivatives with a propylenedioxythiophene (PDOT) moiety as a side-chain. We also synthesized copolymers, poly(PDOT−PV-co-m-SiPhPV), of poly(PDOT−PV) with poly[2-(3-dimethyldodecylsilyphenyl)-1,4-phenylenevinylene], poly(m-SiPhPV), segments. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…[22][23][24][25][26][27] For expanding the synthetic exibility of EDOT a further carbon atom quaternary blocked by alkyl groups has been introduced into the ether bridge 28 giving access to a huge number of derivatives of 3,4-propylenedioxythiophene (Pro-DOT). The corresponding poly(3,4-propylene-dioxythiophene)s (PProDOTs) 29 bearing an alkyl-substituted ether bridge have been employed successfully for color tuning of electrochromic devices, [30][31][32] and for optimising of capacitive behaviour, 33,34 as well as for tailoring of charge-transporting materials in solar cells, [35][36][37][38] the preparation of electroluminescent materials 39 and electro-optic chromophores 40 and as conducting layers in actuators, 41 respectively. Further modication of the alkyl substituents in ProDOT by bromine atoms 42 or a hydroxyl group 43 gives synthetic access to functionalized ProDOTs [44][45][46][47][48] which can be transformed into the related PProDOTs including polymers bearing reactive groups in the side-chain, [49][50][51] useful for designing complex molecular architectures 52,53 and the synthesis of PProDOT hybrid materials, 54,55 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] For expanding the synthetic exibility of EDOT a further carbon atom quaternary blocked by alkyl groups has been introduced into the ether bridge 28 giving access to a huge number of derivatives of 3,4-propylenedioxythiophene (Pro-DOT). The corresponding poly(3,4-propylene-dioxythiophene)s (PProDOTs) 29 bearing an alkyl-substituted ether bridge have been employed successfully for color tuning of electrochromic devices, [30][31][32] and for optimising of capacitive behaviour, 33,34 as well as for tailoring of charge-transporting materials in solar cells, [35][36][37][38] the preparation of electroluminescent materials 39 and electro-optic chromophores 40 and as conducting layers in actuators, 41 respectively. Further modication of the alkyl substituents in ProDOT by bromine atoms 42 or a hydroxyl group 43 gives synthetic access to functionalized ProDOTs [44][45][46][47][48] which can be transformed into the related PProDOTs including polymers bearing reactive groups in the side-chain, [49][50][51] useful for designing complex molecular architectures 52,53 and the synthesis of PProDOT hybrid materials, 54,55 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous publications, we reported the synthesis and characterization of several novel electroluminescent (EL) polymers, including alkylsilylphenyl‐ and alkyloxyphenoxy‐substituted poly(p‐phenylenevinylene)s (PPVs), blend systems with oxadiazole‐containing electron transfer polymers, and the synthesis of alternating copolymers composed of PPV segments and aromatic amine blocks 15–21. More recently, we reported the EL properties of the highly efficient poly(9,9‐dioctylfluorenyl‐2,7‐vinylene) and its copolymers with various feed ratios of poly[2‐methoxy‐5‐(2'‐ethylhexyloxy)‐1,4‐phenylenevinylene] (MEH‐PPV) units,22, 23 and those of PPV with pendant 1,3,4‐oxadiazole and propylenedioxythiophene derivatives obtained with the Gilch polymerization method 24, 25. When BT unit was incorporated into the PF backbone, the concentration was even as low as 10% due to the poor solubility behavior of the resulting copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The copolymerization process has been used widely in the preparation of EL polymers with the aim of achieving a low turn-on voltage, high brightness, high luminance efficiency, and easy tuning of the emission colors as a result of the energy transfer that arises from synergistic effects between the two monomers . In our research in this area, we have previously reported novel EL polymers such as alkyloxyphenoxy and 1,3,4-oxadiazole-substituted PPVs, the blending of systems with 1,3,4-oxadiazole containing electron transfer polymers, the synthesis of alternating copolymers composed of PPV segments and aromatic amine blocks, and poly(9,9-dioctylfluorenyl-2,7-vinylene) and its copolymers with MEH-PPV segments and highly luminescent poly( m -SiPh-PV) derivatives. , Recently, we reported poly(PDOT-PV) and statistical copolymers poly(PDOT-PV- co - m -SiPh-PV) with turn-on voltages in the range of 6.0−9.0 V and a maximum brightness of 5,127 cd/m 2 at 18 V …”
Section: Introductionmentioning
confidence: 99%